Strategi mitigasi risiko pembiayaan pada produk ijarah di bank syariah - Ash Shiddiqi, M. Zidan Fahmi (Maliki Interdisciplinary Journal, 2025)
This study aims to identify and analyze risk mitigation strategies implemented by Islamic banks in financing based on the Ijarah contract. Ijarah, which is a lease agreement involving the transfer of usufruct of an asset, carries unique risks such as asset depreciation, client default, and legal or Shariah compliance risks. This research adopts a qualitative descriptive approach using case studies from several national Islamic banks. Data collection techniques include in-depth interviews with financing practitioners, internal document analysis, and literature reviews on Islamic financial principles. The findings reveal that risk mitigation strategies in Ijarah financing combine contractual, operational, and integrated risk management measures. These include the use of Islamic insurance (takaful), periodic asset valuation, penalty clauses for delays, and additional guarantees or collateral. Furthermore, customer education and awareness are essential to minimize moral hazard. The study concludes that effective risk mitigation in Ijarah financing depends on the synergy between Shariah-compliant product design and adaptive risk management aligned with market dynamics. These findings offer valuable insights for enhancing risk management policies in the Islamic banking sector.